A dog gone murder - Viets, Elaine, 1950- (Viets, Elaine, 1950- Josie Marcus, mystery shopper., 2014)
Josie has been asked to investigate Uncle Bob's Doggy Day Camp, known for its commercials featuring Uncle Bob liking dogs so much that he acts like one. But Josie soon learns how Uncle Bob acts when the cameras are off. Her mother's new tenant, Franklin, who works for Uncle Bob, plans to quit after seeing the man's true nature. But before he gets the chance, Bob is murdered, and Franklin goes from the doghouse to the big house. Now it's up to Josie to clear Franklin's name. Her investigation reveals that Bob was more of a dog than anyone knew--and had been kicked out of his house for bad behavior. As she digs up new clues, Josie will have to catch the killer quickly, before any more trouble is unleashed.